2004
DOI: 10.1002/prot.10624
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of backbone dynamics of monomeric and domain‐swapped stefin A

Abstract: Three-dimensional domain swapping has been observed in increasing number of proteins and has been implicated in the initial stages of protein aggregation, including that of the cystatins. Stefin A folds as a monomer under native conditions, while under some denaturing conditions domain-swapped dimer is formed. We have determined the backbone dynamics of the monomeric and domain-swapped dimeric forms of stefin A by (15)N relaxation using a model-free approach. The overall correlation times of the molecules were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 64 publications
(76 reference statements)
3
13
0
Order By: Relevance
“…This feature is not very surprising, because it is known that in solution N-and C-terminal fragments together with the loops are more Xexible than the core of a protein. This situation was observed in the case of the homologues steWn B, where the N and C termini are more Xexible in the monomer than in the dimer (Japelj et al, 2004). The higher Xexibility of the C-terminal fragment of human cystatin C can be partly explained by NMR studies of the wt and L68Q cystatin C, where the second and the Wfth -strands could be correctly assigned by using CO and C, but not C and H chemical shifts.…”
Section: Discussionmentioning
confidence: 88%
“…This feature is not very surprising, because it is known that in solution N-and C-terminal fragments together with the loops are more Xexible than the core of a protein. This situation was observed in the case of the homologues steWn B, where the N and C termini are more Xexible in the monomer than in the dimer (Japelj et al, 2004). The higher Xexibility of the C-terminal fragment of human cystatin C can be partly explained by NMR studies of the wt and L68Q cystatin C, where the second and the Wfth -strands could be correctly assigned by using CO and C, but not C and H chemical shifts.…”
Section: Discussionmentioning
confidence: 88%
“…At sites of inflammation, cathepsins B, L and S are released during cell death and secreted by activated macrophages, causing the degradation of collagen and elastin, which may lead to ECM remodelling (Reddy et al 1995). Dimerisation of cystatin A that occurs under denaturing conditions (high temperatures 74-93 8C and low pH !2.5; Martin et al 1995, Japelj et al 2004) has been found to inactivate its inhibitory functions. We found a reduced expression of cystatin A 6-23 days before preterm PROM, which may possibly reflect a decrease in fetal membrane integrity due to an increase in unregulated proteolytic activity by cysteine proteinases.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that formation of the domain-swapped dimer of SteA is favoured by heating. 22 The dimeric form of wildtype SteA can be seen in the unheated sample (indicated by an asterisk in Figure 2(a), left-hand panel), increasing significantly following heattreatment (asterisk in Figure 2(a), right-hand panel). As predicted, this dimeric form is undetectable in both STM and STM AU1 (Figure 2(a)).…”
Section: Expression Of Stea Variants In Mammalian Cellsmentioning
confidence: 96%
“…The latter change should both decrease interactions with target proteases and reduce the propensity of the scaffold to dimerize through domain swapping. 22 We refer to the engineered protein with all of these mutations as STM. An illustration of the sequence of the mutated protein with a model sequence (the AU1 peptide, see below) aligned with human StefA is shown in Figure 1(c).…”
Section: Choice Of Site For Peptide Insertionmentioning
confidence: 99%